Spatial-diurnal variability of snow/glacier melt runoff in glacier regime river valley: Central Himalaya, India. (30th May 2021) - Ahluwalia, Rajeev S.; Rai, S.P.; Meetei, Prikash N.; Kumar, Sushil; Sarangi, Shushanta; Chauhan, Pankaj; Karakoti, Indira
Abstract: Spatial-diurnal variability in the snow/glacier melt isotope signature and their influence on hydrograph separation based on mixing model received less attention. We present isotope data from a high elevation catchment (glacierized area: 286 km 2 ) in the central Himalaya (India) and investigated the spatial-diurnal variability of snow/glacier meltwater along with inferences of groundwater dynamics. Isotope signature variation in streamflow was small during the study period. We applied a two-component mixing model using oxygen-18 and electrical conductivity. Hydrograph separation (snow/glacier meltwater and groundwater) was carried out for Bhagirathi River at three sites i.e., Gaumukh, Bhojbasa, and Gangotri, during the ablation period of 2014 (September). The Bhagirathi River is a major tributary of river Ganga, originate from Gangotri Glacier (~30 km), the largest glacier in central Himalaya. The electrical conductivity of the river is measured in-situ and varies from 10 μS/cm to 100 μS/cm. The river water isotope signature of oxygen was ranged from −15.53‰ to −14.32‰ from Gaumukh to Gangotri, snow samples were ranged from - 17.63‰ to - 15.86‰ collected at Gaumukh. Groundwater samples were varied from −8.53‰ to-7.57‰ from Gaumukh to Gangotri. River water signature is close to snow/glacier melt runoff signature, reveal that the snow/glacier melt runoff contribution is higher in river flow. Average fractions of snow/glacier melt runoff were estimated ~82% to~76%, whereas groundwater was estimated ~18% to ~24%. The results of this study reveal the necessity of a multiple sampling approaches to characterize the snow/glacier melt and the importance of groundwater dynamics in catchments with snow/glacial runoff regime. Highlights: Isotopic characterization of diurnalriver water, snow/glacier melt runoff, and groundwater with electrical conductivity in high altitude valley of river Ganga. Estimation to evaluate snow/glacier melt runoff and groundwater interaction in riverusing the isotopic approach.